2022
DOI: 10.3390/ijms23031627
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher Disease Diagnosis Using Lyso-Gb1 on Dry Blood Spot Samples: Time to Change the Paradigm?

Abstract: For years, the gold standard for diagnosing Gaucher disease (GD) has been detecting reduced β-glucocerebrosidase (GCase) activity in peripheral blood cells combined with GBA1 mutation analysis. The use of dried blood spot (DBS) specimens offers many advantages, including easy collection, the need for a small amount of blood, and simpler transportation. However, DBS has limitations for measuring GCase activity. In this paper, we recount our cross-sectional study and publish seven years of experience using DBS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…More recently, a simple and accurate method to determine lyso-Gb1 measurements in DBS samples was established as a useful tool for the screening and diagnosis of GD [ 76 ], while a separate study showed that lyso-Gb1 measured in DBS samples alongside whole-gene sequencing reliably diagnosed GD, although lyso-Gb1 levels did not differentiate between heterozygous GBA1 carriers and wild type [ 77 ]. Nonetheless, Dinur and colleagues proposed a paradigm change for screening patients suspected to have GD based on an analysis of lyso-Gb1 measurements and GBA1 mutation analyses in DBS [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a simple and accurate method to determine lyso-Gb1 measurements in DBS samples was established as a useful tool for the screening and diagnosis of GD [ 76 ], while a separate study showed that lyso-Gb1 measured in DBS samples alongside whole-gene sequencing reliably diagnosed GD, although lyso-Gb1 levels did not differentiate between heterozygous GBA1 carriers and wild type [ 77 ]. Nonetheless, Dinur and colleagues proposed a paradigm change for screening patients suspected to have GD based on an analysis of lyso-Gb1 measurements and GBA1 mutation analyses in DBS [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy parameters included changes in platelet count, plasma levels of hemoglobin, glucosylsphingosine (lyso-Gb1), HDL cholesterol and ferritin, liver and spleen volumes, and bone density (T score of lumbar spine measures by density dual-energy X-ray absorptiometry (DEX)). All efficacy parameters were analyzed locally, whereas lyso-Gb1 was performed at Centogene (Rostock, Germany) as previously reported [ 9 ]. IRB approval was obtained for this retrospective audit.…”
Section: Methodsmentioning
confidence: 99%
“…In mass spectrometric approaches, the marker for GD is the decrease in glucocerebrosidase enzymatic activity [31]. While there are promising studies of using glucosylsphingosine (Lyso-GL1) as a biomarker for individual Gaucher screening [40], it has yet to be tested in a large population-based screen, and further investigation is warranted, especially focusing on its inclusion in larger LSD screening panels. In tandem mass spectrometry (MS/MS), the enzymatic reaction is first performed in the "pre-MS/MS" step before injection into the mass spectrometer to detect enzymatic products.…”
Section: Mass Spectrometry Methodsmentioning
confidence: 99%